Atmospheric-pressure floating electrode-dielectric barrier discharge with flexible electrodes: Effect of conductor shapes - Kim, Jun Hyun; Park, Jin Su; Shin, Yong Seon; Kim, Chang Koo (Korean Journal of Chemical Engineering, 2019)
The plasma characteristics of atmospheric-pressure floating electrode-dielectric barrier discharges (FE-DBDs), which comprised flexible electrodes and were able to generate a plasma along the curvature of skin, were investigated using Cu conductors with various shapes in the flexible powered electrode. These Cu conductors have similar areas but different contour lengths and the shapes of a square, a dumbbell, a star, and a zigzag pattern. The optical intensity and electron temperature of the atmospheric-pressure FE-DBDs increased with the contour length of the conductor used in the flexible powered electrode. This behavior is explained in terms of the changes in the strength of the electric field with the contour length of the conductor, implying that the plasma properties of atmospheric-pressure FE-DBDs with flexible electrodes can be controlled by modulating the contour length or the shape of the electrical conductor in the flexible powered electrode. These results are expected to contribute to the development of an atmospheric-pressure FE-DBD system for plasma medicine.
Keywords: Conductor; Contour Length; Dielectric Barrier Discharge; Flexible Electrode; Plasma; Plasma Medicine